Fiber Optic Sensors and Applications - Tjin, Swee Chuan; Wei, Lei (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue focuses on all aspects of the recent research and development related to fiber optic sensors. The recent advances in fiber-based sensing technologies have enabled both fundamental studies and a wide spectrum of applications. The goal of this Special Issue is to bring attention to the most recent results in the field of fiber optic sensors, including new mechanisms, materials, processes, and applications.